2016
DOI: 10.1016/j.plantsci.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular candidates for early-stage flower-to-fruit transition in stenospermocarpic table grape (Vitis vinifera L.) inflorescences ascribed by differential transcriptome and metabolome profiles

Abstract: Flower-to-fruit transition depends of nutrient availability and regulation at the molecular level by sugar and hormone signalling crosstalk. However, in most species, the identities of fruit initiation regulators and their targets are largely unknown. To ascertain the main pathways involved in stenospermocarpic table grape fruit set, comprehensive transcriptional and metabolomic analyses were conducted specifically targeting the early phase of this developmental stage in 'Thompson Seedless'. The high-throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 82 publications
2
20
0
1
Order By: Relevance
“…Previous reports have mentioned that cyanogenic compounds are highest in growing tissues of plants and that activation of metabolic processes coincide with cyanogenic glycoside production [6,44]. The flower is the main reproductive organ of a plant and has very active and complex morphological and physiological features, which support an abundance of ecological functions related to floral development and plant reproduction [45][46][47]. For instance, de novo synthesis of amino acids, enzymes, and structural proteins, which are precursors of N-containing secondary metabolites (such as cyanogenic glycosides) and signaling molecules, all occur in floral tissues [47].…”
Section: Optimization Of Mixture's Ph For Maximum Generation Of Hydromentioning
confidence: 99%
“…Previous reports have mentioned that cyanogenic compounds are highest in growing tissues of plants and that activation of metabolic processes coincide with cyanogenic glycoside production [6,44]. The flower is the main reproductive organ of a plant and has very active and complex morphological and physiological features, which support an abundance of ecological functions related to floral development and plant reproduction [45][46][47]. For instance, de novo synthesis of amino acids, enzymes, and structural proteins, which are precursors of N-containing secondary metabolites (such as cyanogenic glycosides) and signaling molecules, all occur in floral tissues [47].…”
Section: Optimization Of Mixture's Ph For Maximum Generation Of Hydromentioning
confidence: 99%
“…The results indicated that there are 496 differentially expressed genes and 28 differently metabolic pathways in this process. Their data showed broad transcriptome reprogramming of molecule transporters, globally downregulating gene expression, and suggest that regulation of sugar-and hormone-mediated pathways determines the downstream activation of berry development [4]. Also, the role of gibberellin treatment has been investigated on gene expression changes of grape berries.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…RNA-seq technology is an important method to obtain effective functional genes in crops, especially for crops without reference genomic information. At present, RNA-seq has been widely used to study floral organ development in woody plants [32][33][34][35][36]. With the development of highthroughput sequencing technology, numerous studies have been carried out by SMLRS or in combination with NGS technology.…”
Section: Introductionmentioning
confidence: 99%